Growth Performance of Oil Palm Seedlings (Elaeis guineensis Jacq.) in Response to Palm Oil Waste Compost and Single Inorganic Fertilizer Application in Early Nursery Stages - Oktafianti, Dwi Cantika; Maryani, Anis Tatik; Salim, Helmi (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: The purpose of this study was to determine the response of giving and obtaining the best dose of palm oil waste compost and single inorganic fertilizer on the growth of oil palm seedlings (Elaeis guineensis Jacq.) in early nurseries. This research was conducted at the Teaching and Research Farm of the Faculty of Agriculture, Jambi University for 3 months, starting in March-May 2023. Research Methods: This study used a completely randomized design (CRD) on 5 treatments with 1 factor. Variables observed included plant height (cm), stump diameter (mm), number of leaves (strands), total leaf area (cm2), crown dry weight (g), root dry weight (g), hypothetical vigor index (IVH), and root crown ratio. Finding/Results: The results showed that the application of oil palm waste compost and single inorganic fertilizer (Urea, TSP, KCl) to oil palm nurseries in the early nursery was able to increase the growth of plant height, stump diameter, and number of leaves, but not yet able to significantly increase the growth of total leaf area variables, crown dry weight, root dry weight, hypothetical vigor index, and root crown ratio. The treatment of 150 grams of oil palm waste compost + (Urea, TSP, KCl) half the recommended dose showed the growth of 3-month-old oil palm seedlings in the early nursery.